Kualitas Produk, Pelayanan, dan Loyalitas Pelanggan Dimana Kepuasan Sebagai Variabel Intervening pada UKM Start Up Pariwisata Kombuchi Brewing Co, Bali - Satya Tripayana; Jaya Pramono (JEMAP, 2019)
Research on start-up SMEs in tourism is still very rare. This study explains the effect of product quality and service quality on customer loyalty through customer satisfaction as an intervening variable on 'Kombuchi Brewing Co' as start up company for SMEs in tourism. Survey was conducted by using questionnaires to 120 respondents. Data were analyzed using Path Analysis and Sobel Test. The conclusion of this study stated that product quality and service quality had a positive and significant effect on customer satisfaction. On the other side, product quality and service quality had indirect and significant effect on loyalty through customer satisfaction.